Artist management for the music business - Allen, Paul 1946- (Focal Press, 2015)
Paul Allen prepares you for the realities of successfully directing the careers of talented performers in the high-risk, high-reward music business. You will learn to prepare yourself for a career in artist management and learn the tools to coach, lead, organise time, manage finances, and market an artist.